A dice similarity measure for TBM penetrability classification in hard rock condition with the intuitionistic fuzzy information of rock mass properties - Rui Yong; Jun Ye; Shi-Gui Du; He Zhang; Leiyu Gu; Hang Lin (European Journal of Environmental and Civil Engineering, 2021)

The Identification and Prediction of Mesoscale Eddy Variation via Memory in Memory With Scheduled Sampling for Sea Level Anomaly - Rui Nian; Yu Cai; Zhengguang Zhang; Hui He; Jingyu Wu; Qiang Yuan; Xue Geng; Yuqi Qian; Hua Yang; Bo He (Frontiers in Marine Science, 2021)
Ocean mesoscale eddies are ubiquitous in world ocean and account for 90% oceanic kinetic energy, which dominate the upper ocean flow field. Accurately predicting the variation of ocean mesoscale eddies is the key to understand the oceanic flow field and circulation system. In this article, we propose to make an initial attempt to explore spatio-temporal predictability of mesoscale eddies, employing deep learning architecture, which primarily establishes Memory In Memory (MIM) for sea level anomaly (SLA) prediction, combined with the existing mesoscale eddy detection. Oriented to the western Pacific ocean (125°−137.5°E and 15°−27.5°N), we quantitatively investigate the historic daily SLA variability at a 0.25° spatial resolution from 2000 to 2018, derived by satellite altimetry. We develop the enhanced MIM prediction strategies, equipped with Gated Recurrent Unit (GRU) and spatial attention module, in a scheduled sampling manner, which overcomes the gradient vanishing and complements to strengthen spatio-temporal features for long-term dependencies. At the early stage, the real value SLA input guides the model training process for initialization, while the scheduled sampling intentionally feeds the newly predicted value, to resolve the distribution inconsistency of inference. It has been demonstrated in our experiment results that our proposed prediction scheme outperformed the state-of-art approaches for SLA time series, with MAPE, RMSE of the 14-day prediction duration, respectively, 5.1%, 0.023 m on average, even up to 4.6%, 0.018 m for the effective sub-regions, compared to 19.8%, 0.086 m in ConvLSTM and 8.3%, 0.040 m in original MIM, which greatly facilitated the mesoscale eddy prediction. This proposed scheme will be beneficial to understand of the underlying dynamical mechanism behind the predictability of mesoscale eddies in the future, and help the deployment of ARGO, glider, AUV and other observational platforms.

Increasing nitrogen supply to phosphorus-deficient Medicago sativa decreases shoot growth and enhances root exudation of tartrate to discharge surplus carbon dependent on nitrogen form - Honghua He; Zekun Zhang; Qi Peng; Chao Chang; Rui Su; Xiao Cheng; Yingxin Li; Jiayin Pang; Sheng Du; Hans Lambers (Plant and Soil, 2021)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Selenium-Alleviated Testicular Toxicity by Modulating Inflammation, Heat Shock Response, and Autophagy Under Oxidative Stress in Lead-Treated Chickens - Size Wang; Lulu Hou; Min Wang; Rui Feng; Xu Lin; Shifeng Pan; Qian Zhao; He Huang (Biological Trace Element Research, 2021)

Loganin ameliorates depression-like behaviors of mice via modulation of serotoninergic system - Chen-Hao Pan; Cong-Yuan Xia; Yu Yan; Yan Han; Rui Shi; Jun He; Ze-Xing Wang; Yu-Ming Wang; Wei-Ku Zhang; Jie-Kun Xu (Psychopharmacology, 2021)

Comparative transcriptome analysis reveals that deletion of CheY influences gene expressions of ABC transports and metabolism in Haemophilus parasuis - Lvqin He; Xuefeng Yan; Ke Dai; Xintian Wen; Sanjie Cao; Xiaobo Huang; Rui Wu; Qin Zhao; Yong Huang; Qigui Yan; Xiaoping Ma; Xinfeng Han; et al. (Functional & Integrative Genomics, 2021)

Effects of organic acids on the chemotaxis profiles and biocontrol traits of antagonistic bacterial endophytes against root-rot disease in Panax notoginseng - Li Ma; Wu-Qin Wang; Rui Shi; Xue-Mei Zhang; Xin Li; Yu-Sen Yang; Ming He Mo (Antonie van Leeuwenhoek, 2021)

Rhizosphere-associated nosZII microbial community of Phragmites australis and its influence on nitrous oxide emissions in two different regions - Rui Su; Rui Huang; Jin Zeng; Dayong Zhao; Rujia He; Zhongbo Yu; Qinglong L. Wu (Journal of Soils and Sediments, 2021)

Weakened growth, cell division, and energy metabolism, but enhanced resistance, signaling, and anabolism: responses of Ulva prolifera to copper elucidated by omics - Chuner Cai; Xuanhong Liu; Hui Zhao; Ting Jiang; Rui Jia; Peimin He (Journal of Applied Phycology, 2021)

Structure–activity relationship studies on Pd176252 derivatives leading to discovery of novel GRP receptor antagonist with potent anticancer activity - Ming-jun Yu; Chao Li; Meng He; Yu-ting Zhu; Rui Yang; Sheng-song Deng; Xiao-ming Meng; Ri-sheng Yao (Medicinal Chemistry Research, 2021)

Shifts in Nitrogen Removal Performance and Microbial Communities in Constructed Wetlands After Short-term Exposure to Titanium Dioxide Nanoparticles - Rui Han; Kexin Li; Chenzheng We; Tao He; Jingru Liu; Renduo Zhang; Li Wan; Yinghai Wu (Water, Air, & Soil Pollution, 2021)

On the Mechanism of High-Voltage Pulsed Fragmentation from Electrical Breakdown Process - Xiaohua Zhu; Yunxu Luo; Weiji Liu; Ling He; Rui Gao; Yudan Jia (Rock Mechanics and Rock Engineering, 2021)

Research progress in bioremediation of petroleum pollution - Yong Yang; Zhan-Wei Zhang; Rui-Xia Liu; Hai-Yan Ju; Xue-Ke Bian; Wan-Ze Zhang; Chuan-Bo Zhang; Ting Yang; Bing Guo; Chen-Lei Xiao; He Bai; Wen-Yu Lu (Environmental Science and Pollution Research, 2021)

An eco‐city design methodology for hilly areas of western China - Kai Lin; Zhengwei He; Zhujun Zhao; Jiaxin Chang; Keran Tang; Rui Qu; Li He (Earth Science Informatics, 2021)

Elevated pCO2 Impedes Succession of Phytoplankton Community From Diatoms to Dinoflagellates Along With Increased Abundance of Viruses and Bacteria - Ruiping Huang; Jiazhen Sun; Yunlan Yang; Xiaowen Jiang; Zhen Wang; Xue Song; Tifeng Wang; Di Zhang; He Li; Xiangqi Yi; Shouchang Chen; Nanou Bao; et al. (Frontiers in Marine Science, 2021)
Eutrophic coastal regions are highly productive and greatly influenced by human activities. Primary production supporting the coastal ecosystems is supposed to be affected by progressive ocean acidification driven by increasing CO 2 emissions. In order to investigate the effects of high p CO 2 (HC) on eutrophic plankton community structure and ecological functions, we employed 9 mesocosms and carried out an experiment under ambient (∼410 ppmv) and future high (1000 ppmv) atmospheric p CO 2 conditions, using in situ plankton community in Wuyuan Bay, East China Sea. Our results showed that HC along with natural seawater temperature rise significantly boosted biomass of diatoms with decreased abundance of dinoflagellates in the late stage of the experiment, demonstrating that HC repressed the succession from diatoms to dinoflagellates, a phenomenon observed during algal blooms in the East China Sea. HC did not significantly influence the primary production or biogenic silica contents of the phytoplankton assemblages. However, the HC treatments increased the abundance of viruses and heterotrophic bacteria, reflecting a refueling of nutrients for phytoplankton growth from virus-mediated cell lysis and bacterial degradation of organic matters. Conclusively, our results suggest that increasing CO 2 concentrations can modulate plankton structure including the succession of phytoplankton community and the abundance of viruses and bacteria in eutrophic coastal waters, which may lead to altered biogeochemical cycles of carbon and nutrients.

Oxiracetam Mediates Neuroprotection Through the Regulation of Microglia Under Hypoxia-Ischemia Neonatal Brain Injury in Mice - Dan Wang; Yanbang Wei; Jingxia Tian; Dong He; Rui Zhang; Xiaoshuai Ji; Xiaoming Huang; Jun Sun; Jiajia Gao; Zixiao Wang; Qi Pang; Qian Liu (Molecular Neurobiology, 2021)

Construction and application of easy-to-detect cyanobacteria with vp28 gene - Min-Min Zhuang; Wen Peng; Yang Xu; Xiao-Hui Jia; Ding-Ji Shi; Pei-Min He; Rui Jia (Journal of Applied Phycology, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

Dynamic vertical and rocking impedances of a strip foundation in offshore engineering - Rui He; Jisheng Zhang; Zhen Guo; Weiyun Chen (Marine Georesources & Geotechnology, 2021)

Solid-Fluid Coupled Numerical Analysis of Suction Caisson Installation in Sand - He Wang; Rui Wang; Jian-Min Zhang (Journal of Marine Science and Engineering, 2021)
Suction caissons are widely used foundations in offshore engineering. The change in excess pore pressure and seepage field caused by penetration and suction significantly affects the soil resistance around the caisson wall and tip, and also affects the deformation of the soil within and adjacent to the caisson. This study uses Arbitrary Lagrangian–Eulerian (ALE) large deformation solid-fluid coupled FEM to investigate the changes in suction pressure and the seepage field during the process of the suction caisson installation in sand. A nonlinear Drucker-Prager model is used to model soil, while Coulomb friction is applied at the soil-caisson interface. The ALE solid-fluid coupled FEM is shown to be able to successfully simulate both jacked penetration and suction penetration caisson installation processes in sand observed in centrifuge tests. The difference in penetration resistance for jacked and suction installation is found to be caused by the seepage and excess pore pressure generated during the suction caisson installation, highlighting the importance of using solid-fluid coupled effective stress-based analysis to consider seepage in the evaluation of suction caisson penetration.

The Identification and Prediction in Abundance Variation of Atlantic Cod via Long Short-Term Memory With Periodicity, Time–Frequency Co-movement, and Lead-Lag Effect Across Sea Surface Temperature, Sea Surface Salinity, Catches, and Prey Biomass From 1919 to 2016 - Rui Nian; Qiang Yuan; Hui He; Xue Geng; Chi-Wei Su; Bo He; Amaury Lendasse (Frontiers in Marine Science, 2021)
The population of Atlantic cod significantly contributes to the prosperity of fishery production in the world. In this paper, we quantitatively investigate the global abundance variation in Atlantic cod from 1919 to 2016, in favor of spatiotemporal interactions over manifold impact factors at local observation sites, and propose to explore the predictive mechanism with the help of its periodicity, time–frequency co-movement, and lead-lag effects, via long short-term memory (LSTM). We first integrate evidences yielded from wavelet coefficients, to suggest that the abundance variation potentially follows a 36-year major cycle and 24-year secondary cycle at the time scales of 55 years and 37 years. We further evaluate the responses of Atlantic cod abundance to the external impact factors, including sea surface temperature (SST), catches, prey biomass, and sea surface salinity (SSS), in aid of the wavelet coherence and phase difference, which allows us to identify the dominantly correlative factors and capture the leading roles along the time domain and then divide the responses around the recent 60 years into three stages: before 1985, 1985–1995, and after 1995. At the first stage, the reason for the decline in abundance could be mainly attributed to the rapid rise of fish catches. At the second stage, the impact of SST and SSS also provides significant indices, besides overfishing; meanwhile, the mortality of primary producers and forced migration of fish species indirectly cause the decline. At the third stage, warming SST and growing SSS directly led to the decrease of abundance. Finally, we establish one ensemble of LSTM-SAE architecture to comprehensively reflect the predictive patterns at each stage. It has been demonstrated from experimental results that the models behaved better when intentionally feeding with the dominantly correlative multivariate inputs, instead of either all factors or only the abundance. The proposed scheme provides opportunities to symmetrically identify the underlying predictive attributes of Atlantic cod abundance and potentially perform as the quantitative references in reasonably making fishing decision. With the rapid development in deep learning capabilities, it is hopeful to expect better predictions of the responses to global changes, not only for Atlantic cod but also for other fish species and the ecosystem as a whole.

Numerical simulation of hydraulic properties of soil in the GSPAC system under variable water-levels - Rui Dong; Yu-jiang He (Earth Science Informatics, 2021)

Dyad sex composition effect on inter-brain synchronization in face-to-face cooperation - Yuhua Li; Rui Chen; Ofir Turel; Tingyong Feng; Chao-Zhe Zhu; Qinghua He (Brain Imaging and Behavior, 2021)

Generation and identification of endothelial-specific Hrh2 knockout mice - Rui Meng; Wen-Ke Cai; Wen-Mang Xu; Qiang Feng; Ping Wang; Yan-hua Huang; Yu-Xin Fan; Tao Zhou; Qin Yang; Zhi-Ran Li; Gong-Hao He (Transgenic Research, 2021)

Composition and co-occurrence patterns of Phragmites australis rhizosphere bacterial community - Siwen Hu; Rujia He; Wanjie Wang; Dayong Zhao; Jin Zeng; Rui Huang; Ming Duan; Zhongbo Yu (Aquatic Ecology, 2021)

Contrasting pathways of carbon sequestration in paddy and upland soils - Xiangbi Chen; Yajun Hu; Yinhang Xia; Shengmeng Zheng; Chong Ma; Yichao Rui; Hongbo He; Daoyou Huang; Zhenhua Zhang; Tida Ge; Jinshui Wu; Georg Guggenberger; et al. (Global Change Biology, 2021)
Paddy soils make up the largest anthropogenic wetlands on earth, and are characterized by a prominent potential for organic carbon (C) sequestration. By quantifying the plant‐ and microbial‐derived C in soils across four climate zones, we identified that organic C accrual is achieved via contrasting pathways in paddy and upland soils. Paddies are 39%–127% more efficient in soil organic C (SOC) sequestration than their adjacent upland counterparts, with greater differences in warmer than cooler climates. Upland soils are more replenished by microbial‐derived C, whereas paddy soils are enriched with a greater proportion of plant‐derived C, because of the retarded microbial decomposition under anaerobic conditions induced by the flooding of paddies. Under both land‐use types, the maximal contribution of plant residues to SOC is at intermediate mean annual temperature (15–20°C), neutral soil (pH~7.3), and low clay/sand ratio. By contrast, high temperature (~24°C), low soil pH (~5), and large clay/sand ratio are favorable for strengthening the contribution of microbial necromass. The greater contribution of microbial necromass to SOC in waterlogged paddies in warmer climates is likely due to the fast anabolism from bacteria, whereas fungi are unlikely to be involved as they are aerobic. In the scenario of land‐use conversion from paddy to upland, a total of 504 Tg C may be lost as CO 2 from paddy soils (0–15 cm) solely in eastern China, with 90% released from the less protected plant‐derived C. Hence, preserving paddy systems and other anthropogenic wetlands and increasing their C storage through sustainable management are critical for maintaining global soil C stock and mitigating climate change.

Quartz crystallinity index: New quantitative evidence for biogenic silica of the Late Ordovician to Early Silurian organic-rich shale in the Sichuan Basin and adjacent areas, China - Guoheng Liu; Gangyi Zhai; Rui Yang; Tingpeng He; Bin Wei (Science China Earth Sciences, 2021)

Nitrogen fertilization overweighs intercropping in promotion of dissolved organic carbon concentration and complexity in potato-cropped soil - Ding Wang; Ping Zhao; Rui Xiang; Shuran He; Yanli Zhou; Xinhua Yin; Guangqiang Long (Plant and Soil, 2021)

Protective effect of Lycium barbarum polysaccharide on di-(2-ethylhexyl) phthalate-induced toxicity in rat liver - Rui-jing Liu; Yong-jian He; Huan Liu; Dong-dong Zheng; Shao-wen Huang; Chun-hong Liu (Environmental Science and Pollution Research, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Correction to: Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Effects of oxytetracycline on plant growth, phosphorus uptake, and carboxylates in the rhizosheath of alfalfa - Zekun Zhang; Rui Su; Chao Chang; Xiao Cheng; Qi Peng; Hans Lambers; Honghua He (Plant and Soil, 2021)

Strong phosphorus (P)-zinc (Zn) interactions in a calcareous soil-alfalfa system suggest that rational P fertilization should be considered for Zn biofortification on Zn-deficient soils and phytoremediation of Zn-contaminated soils - Honghua He; Miaomiao Wu; Rui Su; Zekun Zhang; Chao Chang; Qi Peng; Zhigang Dong; Jiayin Pang; Hans Lambers (Plant and Soil, 2021)

Arbuscular mycorrhizal fungus-induced decrease in nitrogen concentration in pore water and nitrogen leaching loss from red soil under simulated heavy rainfall - Yongmei He; Bo Li; Kai Yan; Rui Yang; Gang Lei; Mingrui Li; Yuan Li; Fangdong Zhan (Environmental Science and Pollution Research, 2021)

Association Between Serum Selenium Level and Subclinical Mastitis in Dairy Cattle - Di Wang; Daqing Jia; Ronghe He; Shuai Lian; Jianfa Wang; Rui Wu (Biological Trace Element Research, 2021)

Leaf Transcriptome and Weight Gene Co-expression Network Analysis Uncovers Genes Associated with Photosynthetic Efficiency in Camellia oleifera - Zhilong He; Caixia Liu; Xiangnan Wang; Rui Wang; Yun Tian; Yongzhong Chen (Biochemical Genetics, 2021)

Nocardioides acrostichi sp. nov., a novel endophytic actinobacterium isolated from leaf of Acrostichum aureum - Xiao-Hui Chen; Fei Li; Fei-Na Li; Ming-Sheng Chen; Xiao-Rui Yan; Zi-Bang He; Shun-Lian Li; You-Lang Wu; Li Tuo (Antonie van Leeuwenhoek, 2021)

Long non-coding RNA-based glycolysis-targeted cancer therapy: feasibility, progression and limitations - Rui Liu; Xiaman Wang; Ying Shen; Aili He (Molecular Biology Reports, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Exploring the effects of sociocognitive factors on the adaptation behaviour of farmers in rural Southwest China - Jianjun Jin; Foyuan Kuang; Xinyu Wan; Rui He; Jing Ning (Climate and Development, 2021)

Arbuscular mycorrhizal fungus–induced decrease in phosphorus loss due to leaching in red soils under simulated heavy rainfall - Yongmei He; Rui Yang; Gang Lei; Mingrui Li; Tianguo Li; Fangdong Zhan; Yuan Li (Journal of Soils and Sediments, 2021)

Is small hydropower beautiful? Social impacts of river fragmentation in China’s Red River Basin - Tyler Harlan; Rui Xu; Jun He (Ambio, 2021)

T4 ‐like myovirus community shaped by dispersal and deterministic processes in the South China Sea - Huifang Li; Lu Liu; Yu Wang; Lanlan Cai; Maoqiu He; Long Wang; Chen Hu; Nianzhi Jiao; Rui Zhang (Environmental Microbiology, 2021)
Summary As the most abundant and genetically diverse biological entities, viruses significantly influence ecological, biogeographical and evolutionary processes in the ocean. However, the biogeography of marine viruses and the drivers shaping viral community are unclear. Here, the biogeographic patterns of T4‐like viruses and the relative impacts of deterministic (environmental selection) and dispersal (spatial distance) processes were investigated in the northern South China Sea. The dominant viral operational taxonomic units were affiliated with previously defined Marine, Estuary, Lake and Paddy Groups. A clear viral biogeographic pattern was observed along the environmental gradient from the estuary to open sea. Marine Groups I and IV had a wide geographical distribution, whereas Marine Groups II, III and V were abundant in lower‐salinity continental or eutrophic environments. A significant distance‐decay pattern was noted for the T4‐like viral community, especially for those infecting cyanobacteria. Both deterministic and dispersal processes influenced viral community assembly, although environmental selection (e.g. temperature, salinity, bacterial abundance and community, etc.) had a greater impact than spatial distance. Network analysis confirmed the strong association between viral and bacterial community composition, and suggested a diverse ecological relationship (e.g. lysis, co‐infection or mutualistic) between and within viruses and their potential bacterial hosts.